The Role of Islamic Religious Education Teachers in Fostering Student Learning Creativity - Darwati, Darwati; Ismail, Ismail; Alwi, Usman (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in fostering students’ learning creativity at SMKN 2 Pangkep. Using a qualitative approach with a case study design, data were collected through observation, interviews, and documentation. The analysis involved data reduction, presentation, and conclusion drawing to obtain valid and comprehensive findings. The results show that PAI teachers play several essential roles in the learning process, including those of murabbi (educator and nurturer of character), mu‘allim (provider of knowledge), mu’addib (moral guide), mudarris (classroom teacher), mursyid (spiritual mentor), and ustadz (religious role model). To realize these roles, teachers apply various creative learning strategies such as interactive discussions, project-based and contextual learning, simulations, motivation sessions, and the use of digital media. These methods help create a learning environment that is active, engaging, and conducive to creativity. The study also finds that students demonstrate several forms of creativity, including confidence in expressing opinions, critical and analytical thinking, collaboration, the ability to produce Islamic-based works, and active involvement in religious and social activities. Such outcomes show that creativity in Islamic education is holistic, encompassing intellectual, moral, and spiritual dimensions. Overall, this study highlights the crucial role of PAI teachers in developing students who are not only religiously observant but also creative, innovative, and adaptable to modern educational challenges. The integration of Islamic values with technological advancements strengthens the relevance of Islamic Religious Education in shaping learners with balanced faith, knowledge, and character.